Deadhesion mechanism of commercial unpigmented epoxy and alkyd coating under cathodic polarisation / M.K. Harun and M.Z.A. Yahya - Harun, M.K.; Yahya, M.Z.A. (Faculty of Applied Sciences, 2005)
The wet adhesion behavior of epoxy-polyamide, and alkyd organic coating on silane modified mild steel surface has been studied in an earlier work. Results indicated that 3- Glycidoxypropyltrimethoxy silane (3-GPS) enhanced the wet adhesion of epoxy-polyamide coating and 3-Aminopropyltrirthoxy silane (3-APS) enhanced the wet adhesion of alkyd coating with cohesive failure mode towards the end of the experiment. Cathodic disbonding experiments on these systems indicated that the enhanced adhesion for alkyd, has no effect on their cathodic disbonding behaviour while the use of 3-GPS to enhanced the adhesion of epoxy-polyamide greatly reduced its rate of cathodic disbanding.